2017
DOI: 10.3390/land6040078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Depth and Topography on the Effectiveness of Conservation Practices on Discharge and Soil Loss in the Ethiopian Highlands

Abstract: Abstract:Restoration of degraded landscapes through the implementation of soil and water conservation practices is considered a viable option to increase agricultural production by enhancing ecosystems. However, in the humid Ethiopian highlands, little information is available on the impact of conservation practices despite wide scale implementation. The objective of this research was to document the effect of conservation practices on discharge and sediment concentration and load in watersheds that have diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 49 publications
7
40
0
Order By: Relevance
“…Supporting the current study's findings, Tadesse et al [139] noted considerable improvement in the soil erosion and rehabilitation of degraded lands in the Yezat Watershed of North Western Ethiopia following implementation of integrated watershed development programs. Validating these findings, Akale et al [140] also reported that implementation of upland conservation measures significantly reduced the surface runoff and increased base flow in the Guale and Tikur-Wuha watersheds of the Ethiopian highlands.…”
Section: Discussionmentioning
confidence: 96%
“…Supporting the current study's findings, Tadesse et al [139] noted considerable improvement in the soil erosion and rehabilitation of degraded lands in the Yezat Watershed of North Western Ethiopia following implementation of integrated watershed development programs. Validating these findings, Akale et al [140] also reported that implementation of upland conservation measures significantly reduced the surface runoff and increased base flow in the Guale and Tikur-Wuha watersheds of the Ethiopian highlands.…”
Section: Discussionmentioning
confidence: 96%
“…The model was run to estimate the actual annual rates of soil loss in the study landscape for the years 2000 and 2018. The soil erosion risk within the study area was classified into eight categories, based on previous work by Uddin et al [5], and the estimated mean soil loss rates (t ha −1 y −1 ): very low (< 5), low (5-10), low medium (10)(11)(12)(13)(14)(15), medium (15)(16)(17)(18)(19)(20), high medium (20)(21)(22)(23)(24)(25), high (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), very high (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), and extremely high (>50). Areas with a mean annual soil loss rates lower than low were rated as tolerable soil loss limit [52].…”
Section: Rainfall and Runoff Erosivity Factor (R)mentioning
confidence: 99%
“…Several previous studies highlighted the positive outcome of SWC measures for mitigating erosion risk, restoration of the degraded land while improving the soil fertility and land productivity [5,[35][36][37][38][39][40][41][42][43]. The design and implementation of SWC measures need a spatially intrinsic information on soil loss and severity levels erosion risk [18,47,99].…”
Section: Determination Conservation Priority Levelsmentioning
confidence: 99%
See 2 more Smart Citations